Lesion Distribution and Epidemiology of Mycobacterium bovis in Elk and White-Tailed Deer in South-Western Manitoba, Canada - Todd K. Shury; Doug Bergeson (Veterinary Medicine International)
Surveillance for Mycobacterium bovis in free-ranging elk (Cervus elaphus) and white-tailed deer (Odocoileus virginianus) from south-western Manitoba was carried out from 1997 to 2010 to describe the lesions, epidemiology, and geographic distribution of disease. Tissues were cultured from animals killed by hunters, culled for management, blood-tested, or found opportunistically. Period prevalence in elk was approximately six times higher than deer, suggesting a significant reservoir role for elk, but that infected deer may also be involved. Prevalence was consistently higher in elk compared to deer in a small core area and prevalence declines since 2003 are likely due to a combination of management factors instituted during that time. Older age classes and animals sampled from the core area were at significantly higher risk of being culture positive. Positive elk and deer were more likely to be found through blood testing, opportunistic surveillance, and culling compared to hunting. No non-lesioned, culture-positive elk were detected in this study compared to previous studies in red deer.